The STAT3-Ser/Hes3 signaling axis: an emerging regulator of endogenous regeneration and cancer growth - Poser, Steven W.; Park, Deric M.; Androutsellis-Theotokis, Andreas (Frontiers in Physiology, 2013)
Stem cells, by definition, are able to both self-renew (give rise to more cells of their own kind) and demonstrate multipotential (the ability to differentiate into multiple cell types). To accommodate this unique dual ability, stem cells interpret signal transduction pathways in specialized ways. Notable examples include canonical and non-canonical branches of the Notch signaling pathway, with each controlling different downstream targets (e.g. Hes1 vs. Hes3) and promoting either differentiation or self-renewal. Similarly, stem cells utilize STAT3 signaling uniquely. Most mature cells studied thus far rely on tyrosine phosphorylation (STAT3-Tyr) to promote survival and growth; in contrast, STAT3-Tyr induces the differentiation of neural stem cells. Neural stem cells use an alternative phosphorylation site, STAT3-Ser, to regulate survival and growth, a site that is largely redundant for this function in most other cell types. STAT3-Ser regulates Hes3, and together they form a convergence point for several signals, including Notch, Tie2, and insulin receptor activation. Disregulation and manipulation of the STAT3-Ser/Hes3 signaling pathway is important in both tumorigenesis and regenerative medicine, and worthy of extensive study.